Geo-kinematic investigations in Slovakia and the region of Central and South- eastern Europe based on combination of permanent and epoch-wise GPS networks - HIPMANOVÁ, Linda (Contributions to Geophysics and Geodesy, 2009)
The  region of Central and  Southeastern Europe  is covered  by numerous GPS networks  investigating geo-kinematical behavior of this area.   These  activities  started in early  nineties  within  the several  projects as CERGOP and  CERGOP-2/Environment.  In this  paper  we describe  the process  of combination of four networks located  in the region of Central  and  Southeastern Europe  using  the CATREF (Combination and  Analysis  of Terrestrial REFerence Frame) software  developed  in Institute Geographique National in France.  We  were  particularly interested  in  the CEPER (Central European Permanent Network), CEGRN (Central European Geodynamic Reference  Network), SGRN  (Slovak Geodynamic Reference  Network) and  local  network TATRY  shortly  described in  this paper.  Homogeneous velocity ﬁeld obtained from the ﬁnal combination is for the purpose of better interpretation divided  into three  parts:  Central Europe, Slovakia  and  Tatra Mountains.  Main interest is focused on the territory of Slovakia where the regional velocity ﬁeld is not so frequently discussed  in scientiﬁc  community as the case of Central and Southeastern Europe.